Perlindungan Hukum dan Hak Konstitusional Masyarakat terhadap Dampak Tambang Galian C di Sukolilo Kabupaten Pati - Angga Prastyo Wibowo; Muhammad Zulfikar Amien (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this research is to analyze the legal protection of the constitutional rights of communities affected by the C excavation mine in Sukolilo, especially the importance of protecting community rights and effective law enforcement so that people can avoid the negative impact of mining. So it is necessary to emphasize the importance of this research in providing recommendations for improving regulations or policies that protect communities in mining-affected areas. This research is descriptive research using a qualitative approach with a type of descriptive research aimed at solving problems in the present. This research will examine the constitutional rights of communities in the area of C excavation mining activities, in the Sukolilo area of Pati Regency. The data collection in this research is collected through literature study. This method aims to obtain a strong theoretical foundation and understand the development of relevant recent research, so that the analysis carried out can be more comprehensive and supported by credible scientific references. The formulation of the problems raised are: (1) How are the constitutional rights of people affected by C excavation mining activities in the Sukolilo area of Pati Regency, (2) How are the responsibilities of local governments and mining actors in providing legal protection and guaranteeing the constitutional rights of the Sukolilo community affected by C excavation mining. The results of this study indicate.